CONTRASTING U.S., CHINESE AND RUSSIAN PERCEPTIONS OF SOVEREIGNTY - Ch. Ziegler (Сравнительная политика, 2015)
Abstract: According to realist approach, three most modern influential states Russia, China and US strive to gain maximum freedom in the international arena while retaining independence in domestic policies. The author suggests that a different constructivist approach should be used. Paying attention to the peculiarities of norms and acknowledging the influence of domestic policy on the norms, this approach allows to explain the differences in understanding sovereignty in different states. The political elites of Russia and China tend to consider that the strong central power secures the Westphalian sovereignty, while the historic experience of the US formed the ideal of decentralized power. Aiming at population protection, democracy promotion, terrorist persecution and maintaining US hegemony, American liberal internationalists and neocons are in general eager to step away from the traditional understanding of sovereignty. Russia and China consider sovereignty from the absolutist standpoint, though they have made a number of concessions to the changing norms of territorial integrity and humanitarian intervention. The article proves that the Russian, American and Chinese understanding of sovereignty (both domestic sovereignty and interdependence sovereignty in S.Krasner’s terms) is changing with the emergence of common interests and the necessity to counteract new global threats.